An airflow energy harvester using diamagnetic levitation structure. (February 2019) - Zhang, Kun; Su, Yufeng; Ding, Jianqiao; Gong, Qi; Duan, Zhiyong
Abstract: This paper presents an airflow energy harvester based on diamagnetic levitation structure. A magnet rotor with three teeth evenly distributed on the edge was introduced into the energy harvester, which is freely levitated between highly oriented pyrolytic graphite (HOPG) sheets. A simple prototype of the airflow energy harvester was built, and the performance was tested in various airflow speeds. The experiment results show that the proposed harvester can work stably within an airflow speed range from 0.34 m/s to 9.2 m/s. When the airflow speed was 7.8 m/s, a maximum RMS induced voltage of 61.7 mV was measured and a maximum power output of 31.1 μW was achieved.